Addressing the Challenges of Group Speaking Assessments in the Time of the Coronavirus - Adam Forrester (Cranmore Publishing, 2020)
This paper considers the challenges and possible solutions of moving a group speaking assessment from face-to-face mode to online mode during the coronavirus pandemic from February to May in 2020. The assessment involved 168 higher diploma level students from a range of departments at a tertiary institution in Hong Kong taking their second English subject at university. The students generally have a low level of English (Hong Kong Diploma of Secondary Education level 3). They are in their second semester in their first year at university which runs from September to July each year. The students' first semester was curtailed due to the civil unrest in Hong Kong that led to the closure of the university campus in November 2019. The modified speaking assessment was successfully conducted in early May 2020. Feedback from the English language teachers in the subject was generally positive with the general feeling that students received a more accurate grade as a result of the one-to-one discussion assessment than they had previously received with the group discussion assessment. Grade data appear to confirm this. Student feedback to the modified assessment was mixed with some preferring the original 'group discussion' format while others opting for the revised 'one-to-one discussion' format. Overall, there were some administrative concerns, and the assessment rubric needs to be further modified if the revised format is continued.